Edukasi Interaktif Pengenalan Golongan Obat untuk Meningkatkan Literasi Obat pada Remaja di MTs Al-Hikmah Talang Kelapa - Ulfa Mustofa Nurfadilasari; Josafin Immanuel Siagian (Institut Nalanda, 2026)
Low medication literacy among adolescents may increase the risk of irrational drug use and inappropriate self-medication practices. Adolescents often have access to medicines at home but lack adequate knowledge regarding drug classifications and safe medication use. This community service program aimed to improve medication literacy among students through interactive education on drug classifications at MTs Al-Hikmah Talang Kelapa. The activity involved 24 students using a one-group pretest–posttest design. Educational interventions were conducted through PowerPoint presentations, educational leaflets, direct demonstrations of medicine packaging, interactive discussions, and question-and-answer sessions. Students’ knowledge was evaluated using pre- and post-test questionnaires on drug classifications and safe medication use. The results demonstrated an increase in the mean score from approximately 51 before the intervention to 86 after the intervention, indicating a substantial improvement in students’ understanding of over-the-counter, limited over-the-counter, and prescription drugs. Students also showed increased participation and improved ability to identify medicine logos and distinguish drug categories appropriately. Interactive educational methods supported by visual media and practical demonstrations proved effective in strengthening pharmaceutical literacy among adolescents. This activity is expected to support the development of safe and rational medication practices from an early age.